Aspectos epidemiológicos e clínicos da infecção natural por Trypanosoma cruzi em cães de área endêmica de triatomíneos monitorados pela vigilância epidemiológica no sul do Espírito Santo - Pontes, Beathriz Giostri (2020)
Chagas disease (CD) is an anthropozoonosis with high morbidity and mortality mainly in endemic countries in Latin America.The protozoan Trypanosoma cruzi, an etiological agent of CD, is present in the endemic regions of several species of triatomines (vec